Tubulointerstitial Nephritis Accompanying Gamma-Heavy Chain Deposition and Gamma-Heavy Chain Restricted Plasma Cells in the Kidney (Iranian Journal of Kidney Diseases, 2014)
Monoclonal immunoglobulin heavy chain (HC) diseases are rare proliferative disorders of B lymphocytes or plasma cells characterized by the presence of monoclonal α-, µ-, or γ-HC without associated light chains in the blood, urine, or both. We report a 59-year-old woman with a history of Hodgkin disease who developed hypercalcemia, proteinuria, and impaired kidney function. Protein electrophoresis and immunofixation displayed γ-HC without associated light chains in the serum and urine. Pathologic examination demonstrated severe tubulointerstitial nephritis associated with diffuse and strong linear staining of the glomerular and tubular basement membranes as well as Bowman capsules for γ-HC, but not for κ- or λ-light chains. Immunohistochemical examination of the kidney and bone marrow demonstrated numerous CD138+ plasma cells immunoreactive for γ-HC, but not for κ- or λ-light chains. This is the first report of tubulointerstitial nephritis associated with γ-HC deposition and γ-HC restricted plasma cells in the kidney. This report heightens awareness about tubulointerstitial nephritis as a possible manifestation of γ-HC deposition in the kidney.